2014
DOI: 10.1177/1090198114537067
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Use of Technology for Reminiscence Therapy

Abstract: As the segment of the population 65 years of age or older continues to grow, the number of individuals with dementia increases proportionally, highlighting the need to design therapies that meet the social and emotional needs of people with dementia. Information and communication technologies (ICT) are potential venues for supporting the delivery of such therapies, including reminiscence therapy (RT), which is a non-pharmacological intervention involving the prompting of past memories, often with artifacts suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
146
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(172 citation statements)
references
References 54 publications
(62 reference statements)
11
146
0
4
Order By: Relevance
“…One of the challenges faced by seniors is increasing social isolation from family and friends as they age [7]. It is common for seniors to develop age-related cognitive impairments as they grow older.…”
Section: Benefits Of Reminiscence For Older Adultsmentioning
confidence: 99%
“…One of the challenges faced by seniors is increasing social isolation from family and friends as they age [7]. It is common for seniors to develop age-related cognitive impairments as they grow older.…”
Section: Benefits Of Reminiscence For Older Adultsmentioning
confidence: 99%
“…Concerning mental and behavioral disorders, six studies were retrieved: two studies [18,34] reported on the use of videoconferencing [18] and interactive web-based applications [34] to support people with psychosis; two studies [15,54] reported on the use of videoconferencing [15], interactive web-based applications [15], and computer-based applications [54] to support patients with depression; one study reported on the use of computer-based applications [24] to support patients with insomnia, and another study reported on the use of interactive web-based applications and computer-based applications [37] to support patients with dementia.…”
Section: Mental and Behavioral Disordersmentioning
confidence: 99%
“…Finally, one study report on the use interactive web-based applications and computer based applications to support people with dementia, and promote their participation and social interactions (e.g., to take ownership of conversations) [37]. However, the high variability of the primary studies' design and respective aims made a quantitative determination of how different aspects of might contribute very difficult [37].…”
Section: Mental and Behavioral Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…psychosis, depression or dementia). The literature reports the effectiveness of different remote treatments and highlights participant satisfaction (Alvarez-Jimenez et al 2014;García-Lizana and Muño-Mayorga, 2010;Highton-Williamson, Priebe and Giacco, 2015;Lazar, Thompson and Demiris, 2014;Richards and Richardson, 2012;Sharp, Kobak and Osman, 2011). Although several reviews of reviews and meta-analysis related to technologies for ageing in place reported studies focusing on older adults with chronic diseases, there is a lack of systematized evidence of the state of the art research when looking for community-dwelling older adults without specific chronic conditions.…”
Section: Related Workmentioning
confidence: 99%